Collective strategies to cope with work related stress among nurses in resource constrained settings: An ethnography of neonatal nursing in Kenya. (January 2020) - McKnight, Jacob; Nzinga, Jacinta; Jepkosgei, Joyline; English, Mike
Abstract: Kenyan neonatal nurses are asked to do the impossible: to bridge the gap between international standards of nursing and the circumstances they face each day. They work long hours with little supervision in ill-designed wards, staffed by far too few nurses given the pressing need. Despite these conditions, a single neonatal nurse can be tasked with looking after forty sick babies for whom very close care is a necessity. Our 18-month ethnography explores this uniquely stressful environment in order to understand how nurses operate under such pressures and what techniques they use to organise work and cope. Beginning in January 2015, we conducted 250 h of non-participant observation and 32 semi-structured interviews in three newborn units in Nairobi to describe how nurses categorise babies, balance work across shifts, use routinised care, and demonstrate pragmatism and flexibility in their dealings with each other in order to reduce stress. In so doing, we present an empirically based model of the ways in which nurses cope in a lower-middle income setting and develop early work in nursing studies that highlighted collective strategies for reducing anxiety. This allows us to address the gap left by prevalent theories of nursing stress that have focused on the personal characteristics of individual nurses. Finally, we extend outwards from our ethnographic findings to consider how a deeper understanding of these collective strategies to reduce stress might inform policy, and why, even when the forces that create stress are alleviated, the underlying model of nursing work may prevail. Highlights: Describes the understudied environment of LMIC inpatient newborn wards. Details how stress is managed through the design and enactment of nursing work. Develops and extends early theories of nurses' collective coping methods. Offers an alternative to questionnaire-based understandings of nursing stress. Links low-resource environments to nurse coping mechanisms.